NURSING CARE IN ADMINISTRATING OPIOIDS IN THE POST-OPERATORY OF TOTAL HIP ARTROPLASTY - Meriane Amorim da Costa (Universidade Federal do Paraná, 2000)
The present work is the result of quantitative research. Its objectives are to relate the daily duties of the nursing team as well as their knowledge relating to nursing care in the administration of opioids in the post-operatory of total hip artroplasty. It shows that training strategies need to be repeated and new evaluation must take place. The research reveals significant diagnosis for the improvement of assistance and reduction of risks to patients.